Vaccine effectiveness evaluation during a varicella outbreak among children of primary schools and day-care centers in a region which adopted UMV - Tafuri, Silvio (Landes Bioscience, 2013)
This study describes an outbreak of varicella, in a small town in the region of Puglia, Southern Italy, in the period between February–March 2011. This outbreak presented the opportunity to assess varicella vaccine effectiveness and its determinants. The outbreak occurred in a small community in Puglia; parents of the children attending the schools of the community were contacted by telephone and information was gathered on current disease and varicella history. Varicella vaccination history was verified through the immunization registry of the Local Health Unit. Before the outbreak, immunization coverage was 86.6% of children attending preschool and 51.9% of children attending elementary school. In day care center where the outbreak was happened, the attack rate in vaccinated individuals was 32.1% and 80% in susceptible unvaccinated individuals. VE is therefore estimated as 59.9% (95% CI = 48.3–69.8). In the elementary school the VE can be calculated as 69.2% (95% CI = 50.5–88.1), since the attack rate in unvaccinated children was of 23.1% and in vaccinated of 7.1. The time between vaccination and the onset of the epidemic appears higher in children with a vaccine failure. The results of this study highlight the need for a reflection on the desirability of adopting a shorter schedule in Italy, with a minimum 1 mo interval between MMRV doses.